Combined Effect of vanillin enriched with calcium lactate on tomato (Lycopersicon esculentum var. esculantum) quality - Gunavathy Selvarajh (2016)
This study was conducted to examine combined effects of calcium lactate (l% or 2%) and vanillin (0.3% or 0.5%) treatments on shelf life of tomato fruits (Lycopersicon esculentum) stored at ambient temperature (28 ⁰C) for 12 days. It was found that calcium lactate and vanillin treatments enhanced the shelf life and postharvest quality of tomato fruits. The effectiveness of these two compounds in extending tomato shelf life was evaluated with four different concentrations, 1% CL+0.3% VN, 1% CL+0.5% VN, 2% CL+0.3% VN and 2% CL+0.5% VN. Treated tomatoes showed a better performance in visual quality, weight loss, ﬁrmness, total soluble solid and colour compared to untreated fruits. 2% CL+0.5% VN concentration effectively delayed the senescence of tomatoes fruits which associated with colour, ﬁrmness and shrinkage. During 12th days of storage, this concentration exhibited lower percentage of weight loss, 1.70% compared to untreated tomato. At this concentration also, a less chance of disease occurrence and low total soluble solid was observed. Vanillin-calcium lactate coating can be a good potential alternative coating to preserve quality and extend the shelf life of tomato fruits.